Open access medical publications - Grouse, Lawrence (Journal of Thoracic Disease, 2014)
Open access journals provide unrestricted, free online access to scholarly articles (1). This new approach to medical publication is revolutionizing medical communications. The rise of open access publishing challenges the long-standing model developed in concert by commercial publishers and medical organizations, a model whose profitability depends on the ability to restrict and sell access the medical information and to use this information for political and financial purposes.